Bal Ex Module with Prayer Regimes Improves Standing Dynamic Balance of balance disorders cases - Zuraida Zainun; Munzir Zuber; Hussein Waheeda-Azwa; Dr Juhaida Daud; Muzaimi Mustapha; Zamzuri Idris; Ibtisam Al Sulaimi; Ayida A. Rhaim Al Bulushi (International Journal of Brain Sciences, 2025)
Integrating prayer regimes into balance rehabilitation, a well-established approach for patients with balance disorders offers an intriguing dimension to the therapy that had been incorporated in this Bal Ex Homebased video module for balance rehabilitation. Vestibular rehabilitation, often exemplified by Cawthorne-Cooksey exercises and their customized variants, effectively addresses symptoms like vertigo and instability. However, it's important to approach the inclusion of spiritual practices with sensitivity, acknowledging patients' diverse beliefs and ensuring inclusivity. Consulting healthcare professionals specialized in vestibular rehabilitation is essential to ensure that these additional elements harmonize with the primary therapeutic goals and are backed by scientific evidence, ultimately enhancing overall patient well-being and complementing the rehabilitation process. In this study, 10 subjects were recruited who underwent virtual balance rehabilitation. Upon the completion of these vestibular rehabilitation therapy sessions which were done virtually, the improvement recovery percentage among patients is 90 % or more. The Bal Ex foam test and psychological test using questionnaires were improved as well. The study has effectively shown how virtual or online therapy of balance treatment using Bal Ex Module with Prayer Regimes can benefited balance disorders cases by improves Standing Dynamic Balance and reduce the vertigo symptoms.
Keywords: Balance rehabilitation; Rehabilitation; Vestibular rehabilitation; balance disorder; poor compliance; prayer; prayer movement; vertigo; virtual clinic